Larvicidal effects and phytochemical evaluation of essential oils of Trachyspermum ammi and Ziziphora clinopodioides against larvae Anopheles stephensi - Hanieh Torabi-Pour; Mansoureh Shayeghi; Hasan Vatandoost; Mohammad-Reza Abai (Shahrekord University of Medical Sciences, 2017)
Introduction: The main purpose of this research was to evaluate larvicidal effects of two native medicinal plants in Iran including seeds of Ajwain (Trachyspermum ammi) and leaves and shoots of Blue Mint Bush (Ziziphora clinopodioides) against larvae of Anopheles stephensi. Their phytochemical compounds of essential oils were also determined using GC-MS method. Methods: The plants were collected from various regions of the country in the spring of 2013, and the aqueous essential oils were prepared using a Clevenger apparatus. The standard WHO method for anti-larval experiments against third and fourth instar larvae of A. stephensi was employed at the Biometric Laboratory next to the Culicidae Insectarium at the School of Public Health of Tehran University of Medical Sciences. Results: The LC50s (lethal concentrations to kill 50%) and LC90s of the essential oils were 14.26 and 39.54 ppm T. ammi and 18.61 and 48.51 ppm for Z. clinopodioides. Phytochemical analysis of the essential oils of the tested plants revealed that thymol for T. ammi and pulegone for Z. clinopodioides had the highest percentage which were 71.989 and 48.609, respectively. Conclusion: Considering the results of this research, the effective compounds in these essential oils that had larvicidal properties might be used against malaria vectors.